The impact of cartels on national economy and competitiveness : a Lithuanian case study /: a Lithuanian case study. (2015) - Bruneckiene, Jurgita, 1978-; Pekarskienė, Irena; Guzavičius, Andrius; Palekienė, Oksana; Šovienė, Jūratė
No abstract available